2020
DOI: 10.15766/mep_2374-8265.10887
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology Handoff Simulation Case: A Handoff From Intensive Care Unit to Operating Room for Anesthesiology Learners

Abstract: Introduction:Handoffs have been shown to be a potential cause of communication failures, leading to possible inefficiencies and patient harm. We noticed that our CA-1 residents were struggling with patient handoffs and designed this simulation to improve their handoff skills. Methods: This anesthesiology-specific simulation introduced learners to the perioperative handoff process. We designed it for anesthesiology learners, including junior residents, medical students, and student nurse anesthetists. The simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The group that implemented the SWITCH program experienced greater improvement in their perceptions of nursing job performance, attitude, and nursing process adoption skills compared with the control group. These results are similar to those of previous studies showing improvements in understanding of clinical situations, knowledge of key hand‐off information, and hand‐off skills after a simulated hand off 41 . However, because these are subjective perceptions rather than objective measurements, we could not confirm whether the subjective perception of improvements translates to actual improvements in job performance.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The group that implemented the SWITCH program experienced greater improvement in their perceptions of nursing job performance, attitude, and nursing process adoption skills compared with the control group. These results are similar to those of previous studies showing improvements in understanding of clinical situations, knowledge of key hand‐off information, and hand‐off skills after a simulated hand off 41 . However, because these are subjective perceptions rather than objective measurements, we could not confirm whether the subjective perception of improvements translates to actual improvements in job performance.…”
Section: Discussionsupporting
confidence: 67%
“…These results are similar to those of previous studies showing improve ments in understanding of clinical situations, knowledge of key hand-off information, and hand-off skills after a simulated hand off. 41 However, because these are sub jective perceptions rather than objective measurements, we could not confirm whether the subjective perception of improvements translates to actual improvements in job performance. A recent study showed that even after using a standardized bedside hand-off tool, there was no reduction in the incidence of adverse events or improved outcomes for patients.…”
Section: Discussionmentioning
confidence: 90%